2009
DOI: 10.1111/j.1744-1609.2009.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Using all the available evidence: perceptions of paediatric occupational therapists about how to increase evidence-based practice

Abstract: Participants in this study perceived that although it is necessary to use all the available evidence in practice settings, there are currently barriers to using both research-based and practice-based evidence. In particular, the study indicates that there is need for the development of a structured model with processes and standards to guide practitioners in the collection, trial, evaluation and dissemination of practice-generated evidence. Further research is needed to explore the extent to which valid eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 13 publications
1
28
0
1
Order By: Relevance
“…Difficulties with determining how to best transfer research knowledge into treatment of the unique and individual patient, is however, also an issue that has been reported in previous qualitative studies among graduated clinicians [38,39]. Thus, it is perhaps less surprising that undergraduate students in this study found it difficult to determine if research evidence was valid and applicable; bearing in mind their modest amounts of clinical experience.…”
Section: Discussionmentioning
confidence: 83%
“…Difficulties with determining how to best transfer research knowledge into treatment of the unique and individual patient, is however, also an issue that has been reported in previous qualitative studies among graduated clinicians [38,39]. Thus, it is perhaps less surprising that undergraduate students in this study found it difficult to determine if research evidence was valid and applicable; bearing in mind their modest amounts of clinical experience.…”
Section: Discussionmentioning
confidence: 83%
“…La experticia clínica, una de las piedras angulares de la PBE, ha sido identificada como uno de los principales recursos de información usados por terapeutas ocupacionales para tomar decisiones clínicas (Copley & Allen, 2009), consistente con los hallazgos de este estudio. Los participantes señalaron usar frecuentemente su intuición y opinión personal para tomar decisiones en la práctica, independiente de los años de experiencia profesional que posean, lo cual contrasta con la literatura que señala que con menos experiencia clínica, los terapeutas debieran guiarse en base a literatura y conocimiento disponible, y no en base a su intuición.…”
Section: Discussionunclassified
“…Reported common barriers to implementing EBP by these occupational therapists mirrored findings in other allied health professions. Barriers were focused on the process of finding appropriate evidence and implementing it, including difficulty defining a clinical question; limited searching and appraisal skills; lack of confidence, training, and familiarity with search strategies; difficulties in using databases, difficulty understanding research terminology, statistics, and critical appraisal skills; a perceived lack of evidence to support the use of specific interventions; and uncertainty if the evidence was applicable to clients and practice (Copley & Allen, 2009;Crabtree et al, 2012;Fruth et al, 2010;Graham et al, 2013;Hankemeier & Van Lunen, 2011;Stronge & Cahill, 2012). In addition, there are environmental barriers, such as lack of time or money to pursue EBP, large caseloads, poor organizational support, limited access to published information, and poor patient compliance (Crabtree et al, 2012;Fruth et al, 2010;Stronge & Cahill, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%